HUBUNGAN FAKTOR HUMAN, ORGANIZATION DAN TECHNOLOGY (HOT-FIT MODEL) DENGAN KINERJA SISTEM INFORMASI MANAJEMEN FARMASI DI RUMAH SAKIT BWT SEMARANG - Anik Sholistiyawati; Atik Mawarni; Yudhy Dharmawan (Jurnal Kesehatan Masyarakat (Undip), 2020)
Pharmacy management information system is the application of an organized system for inputting, processing and presenting data to support the information needed by users in pharmaceutical services. At Bhakti Wira Tamtama Hospital, there are problems related to pharmaceutical management information systems such as frequent system disruptions, inaccurate drug stock in applications and in warehouses, etc. So it is necessary to improve the performance of pharmaceutical management information systems by knowing the variables contributed so that the intervention can be done on these variables. Based on previous research that also used the HOT-Fit method to evaluate information systems, the purpose of this study is to knowing that there is a relation between human, organization and technology with the performance of pharmaceutical management information systems. The method used is explanatory research using cross sectional. The subjects of this study used a total population of 14 respondents. The result of this study shows that there is a relation between technology and human (p = 0.021), technology and organization (p = 0.0001), human and organization (p = 0.006) and human and information system performance (p = 0.005), while there is no relation between organization and performance pharmaceutical management information system (p = 0.530). Recommendation for hospitals need to improve exciting features include drug stock features to function properly and add new features such as editing features.